Beyond cardiovascular medicine: potential future uses of icosapent ethyl. (6th October 2020) - Bhatt, Deepak L; Hull, Mark A; Song, Mingyang; Van Hulle, Carol; Carlsson, Cindy; Chapman, M John; Toth, Peter P
Abstract: The REDUCE-IT trial demonstrated that icosapent ethyl, an ethyl ester of eicosapentaenoic acid (EPA), reduced cardiovascular events in an at-risk population by a substantial degree. While the cardiovascular protective properties of this compound are now proven, several other potential uses are being actively explored in clinical studies. These areas of investigation include cancer, inflammatory bowel disease, infections, Alzheimer's disease, dementia, and depression. The next decade promises to deepen our understanding of the beneficial effects that EPA may offer beyond cardiovascular risk reduction.